The Implementation of The Millionaire Club Indonesia Business in Achieving Maqoshid Syariah - Rahmat Kurniawan; Hijja Mardhiya Nasution; Ricka Dinda Safira (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of community service activities is to find out the form of millionaire club Indonesia's business operations in the community and to find out the implementation of millionaire club Indonesia's business in achieving Maqoshid Syariah. This community service activity was carried out on April 23, 2022 using the seminar method. The informants in this study were cadres of the Islamic Student Association commissariat of the Faculty of Social Sciences Deli Serdang Branch totaling 25 people. The results of this community service activity can be concluded that the operational form of MCI is selling health and beauty products that already have halal MUI and BPOM certificates by carrying out 7 positive habits known as 7 Victorious Person and the participants can understand the material presented and get alternative solutions in running an MCI business to achieve sharia maqoshid.